Towards the development of reliable and economical mHealth solutions: A methodology for accurate detection of Buruli ulcer for hard-to-reach communities - Queen, Courtney M.; Hu, Rui; Zouridakis, George (Frontiers in Tropical Diseases, 2023)
mHealth interventions have the potential to increase access to healthcare for the most hard-to-reach communities. For rural communities suffering disproportionately from skin-related NTDs, and Buruli ulcer, there is a need for low-cost, non-invasive and mobile tools for the early detection and management of disease. Dermoscopy is a noninvasive in-vivo technique that has been useful in improving the diagnostic accuracy of pigmented skin lesions based on anatomical features and morphological structures of lesions. Objectives Using dermoscopy, this study develops the automated tools necessary for developing an effective mHealth intervention towards identifying BU lesions in the early stages. Methods: This imaging methodology relies on an external attachment, a dermoscope, which uses polarized light to cancel out skin surface reflections. In our initial studies we used a dermoscope with only crosspolarized white-light (DL100, 3Gen) but later we adopted a more advanced multispectral dermoscope (DLIIm, 3Gen). The latter employed additional monochromatic light at different wavelengths of the visible spectral range, specifically blue (470 nm), yellow (580 nm), and red (660 nm) color, to visualize pigmented structures of skin layers at different depths. Results Results obtained using a subset of 58 white-light images with confirmed diagnosis (16 lesions BU and 42 lesions non-BU) resulting in sensitivity of 100 and specificity of 88.10, with an overall accuracy of 94.05 at 95% CI. Performance obtained using a second dataset of 197 dermoscopic multispectral images (16 lesions BU and 181 lesions non-BU) resulted in sensitivity of 90.00% and specificity of 93.39% with a balanced accuracy of 91.69% (86.95% to 95.12% at 95% CI). Conclusions This system will continue to perform even as the technology evolves and newer dermoscopes are available. Subsequent studies involve the DL4 which provides more uniform and brighter illumination, higher lesion magnification, and wider field of view which, combined with the superb resolution of modern smartphones, can result in faster and more accurate lesion assessment. This is an important step for the development of mHealth tools for use by non-specialists in community settings for the early detection of Buruli ulcer, skin-NTDs, and other dermatologic conditions associated with disease, including wound healing and management of disease progression.